2021
DOI: 10.18510/hssr.2021.9369
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Formative Assessment Practices Implemented in English Language Learning Programs in Sindh

Abstract: Purpose of the study: The purpose of this study is to explore the merits and demerits of a formative assessment technique used in an English language learning program in Sindh. The teachers teaching the English language to the students of rural Sindh in an English language program implemented a formative assessment technique and in the end, shared their views about the effectiveness of the program. Methodology: The research is based on a qualitative method. Formative assessment was conducted in a languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A critical review of forms of assessment of practical activities in the structure of curricula in other disciplines, including foreign languages [20] found that testing as a form of assessment showed objective results. A clear and non-subjective approach to grading is eff ective, and there is a link between high scores, student achievement, and additional motivation and a desire to improve through constructive feedback.…”
mentioning
confidence: 99%
“…A critical review of forms of assessment of practical activities in the structure of curricula in other disciplines, including foreign languages [20] found that testing as a form of assessment showed objective results. A clear and non-subjective approach to grading is eff ective, and there is a link between high scores, student achievement, and additional motivation and a desire to improve through constructive feedback.…”
mentioning
confidence: 99%